2019
DOI: 10.1186/s13104-019-4633-1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot prospective study of sleep patterns and DNA methylation-characterized epigenetic aging in young adults

Abstract: Objective Molecular markers in DNA methylation at a subset of CpG sites are affected by the environment and contribute to biological (epigenetic) age. We hypothesized that shorter sleep duration and possibly irregular sleep would be associated with accelerated epigenetic aging. We examined epigenetic vs. chronological age in 12 young women selected as shorter or longer sleepers studied prospectively across the first 9 weeks of college using a daily online sleep log. Genomic DNA was isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 16 publications
0
22
3
Order By: Relevance
“…Acceleration of the DNAmAge clock has been associated with insomnia in a sample of 2078 women [ 27 ]. Carskadon et al [ 28 ] found an association between poor quality / fewer hours of sleep with age acceleration in a small sample of 12 female college students.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration of the DNAmAge clock has been associated with insomnia in a sample of 2078 women [ 27 ]. Carskadon et al [ 28 ] found an association between poor quality / fewer hours of sleep with age acceleration in a small sample of 12 female college students.…”
Section: Introductionmentioning
confidence: 99%
“…Acceleration of the DNAmAge clock has been associated with insomnia in a sample of 2078 women (Carroll et al, 2017). Carskadon et al (2019) found an association between poor quality / fewer hours of sleep with age acceleration in a small sample of 12 female college students.…”
Section: Introductionmentioning
confidence: 86%
“…Of course, this finding does not indicate that these genes are involved in psychological function, merely that they were differentially modified in shorter sleepers. More recently, we showed that epigenetic modifications of DNA obtained from blood samples before and after sleep phenotyping occurred in relation to the combination of short and irregular sleep (Carskadon et al, 2019) and that these changes combined to signify ‘epigenetic aging’ in these young adults. Again, these data do not indicate a direct connection to psychopathology; however, future studies that have larger samples and that assess specific pathways affected may be able to provide connections.…”
Section: Figurementioning
confidence: 99%